The Power of Employing Science and Diverse Arts for Immersive, Sensory Food Education: A Case Study of Tiistenjoki Elementary School - Juhola, Katja; Kelly, Joan; Hopia, Anu Inkeri (Routledge, 2026)
In this article, we present how arts-based methods can facilitate the exploration of children’severyday food experiences, emphasizing nonverbal expressions of feelings and values.Through a case study of an international collaboration in food and socially engaged art (SEA)led by Finnish artist and researcher Katja Juhola, our study highlights the intersection of art,community engagement, and food education. With a strong commitment to diversity andrespect for all participants, Juhola’s research planning revolved around the theme of food,particularly relevant in an area where agricultural work is central to family life.